2018
DOI: 10.1021/acsomega.8b00389
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation-Induced Biomolecule Detection on Versatile Superhydrophilic Patterned Surfaces: Glucose and DNA Assay

Abstract: We introduce a droplet-based biomolecular detection platform using robust, versatile, and low-cost superhydrophilic patterned superhydrophobic surfaces. Benefitting from confinement and evaporation-induced shrinkage of droplets on wetted patterns, we show enrichment-based biomolecular detection using very low sample volumes. First, we developed a glucose assay using fluorescent polydopamine (PDA) based on enhancement of PDA emission by hydrogen peroxide (H2O2) produced in enzyme-mediated glucose oxidation reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Meanwhile, Beyazkilic et al reported a superwetting platform as glucose biosensor depending on the fluo-rescent PDA (Figure 10g-i). [195] The PDA emission could be enhanced by H 2 O 2 , the product of glucose oxidation reaction, providing a powerful tool for glucose detection. In addition, the enrichment capacity of superhydrophilic patterned superhydrophobic substrate imparted the biosensor with increased reaction rate and sensitivity.…”
Section: Glucose Detectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Meanwhile, Beyazkilic et al reported a superwetting platform as glucose biosensor depending on the fluo-rescent PDA (Figure 10g-i). [195] The PDA emission could be enhanced by H 2 O 2 , the product of glucose oxidation reaction, providing a powerful tool for glucose detection. In addition, the enrichment capacity of superhydrophilic patterned superhydrophobic substrate imparted the biosensor with increased reaction rate and sensitivity.…”
Section: Glucose Detectionmentioning
confidence: 99%
“…To solve these, researchers have dedicated to developing biomaterials with specific wettability, together with adding antibacterial ingredients for further treatment. Up to date, medical dressings based on biomaterials with specific wettability have demonstrated values in accelerating the wound healing process through removing excessive biofluid around wounds, [ 96 , 174 ] inhibiting adhesion of harmful biomolecules, [ 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 , 197 , 198 , 199 , 200 , 201 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 ,…”
Section: Biomaterials and Tissue Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…Ren et al, used a PDMS-made SHS treated by CF 4 /O 2 plasma to increase superhydrophobicity as a concentrator of DNA for high-dilution detection [117]. Other authors have obtained an analogous result on DNA or other molecules using a disordered SHS [118,119]. A SEM picture of a pillar realized on silicon is shown in (F), which has a dual-electrode sensor fabricated on its top and contacted for electrical measurements.…”
Section: Shs For Manipulation Of Dna and Proteinsmentioning
confidence: 99%